Dr. Haljecka Eva MD (1869–1947) first female surgeon and gynecologist in Serbia - Babić, Strahinja; Marjanović, Aleksandra; Stanković-Babić, Gordana; Babić, Nevena; R. Babić, Rade (Medical Word, 2021)
Dr. Eva Haljecka, a Jew of Polish origin, was born on 1869 in Poland, died on 1949 in Yugoslavia, Belgrade, was the first woman surgeon and gynecologist-obstetrician in Serbia and Yugoslavia. Carried out on 1910 the first caesarean section in Niš. She was a duty manager in district hospital in Niš in three occasions – during the Balkan wars, in the World War I and after the World War I. Dr. Eva Haljecka was the first woman doctor of that time in Serbia who seek the full equality beetween male and female doctors and she was awarded for that. German newspaper Illustrirte Zeitung wrote about her and also about other women doctors – Draga Ljočić, Darinka Maletić-Banković, Marija Vučetić-Prita and Ljubica Đurić. Dr. Eva Haljecka accepted Serbia as a new homeland and made it for her all that he could.
Keywords: Dr. Eva Haljecka, gynecologist-obstetrician, surgeon, Serbia